Biomedical engineering education at Politecnico di Milano: Development and recent changes - Baselli, G (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2009)
Abstract The biomedical engineering (BME) programme at the Politecnico di Milano (POLIMI) is characterized by a strong interdisciplinary background in a broad range of engineering subjects applied to biology and medicine. Accordingly, the undergraduate level (3 years) provides a general education, which includes mechanics, chemistry and materials, electronics, and information technology both in the context of general engineering and within BME foundations. In contrast, the postgraduate programme (2 years) offers a broad choice of specializations in BME fields in close connection with the BME research activities and laboratories of the campus and with active interchange with the other engineering disciplines. The history of BME development at POLIMI is briefly recalled, together with the characteristics of educational and research work, which is strongly biased by a large polytechnic university with no medical school within the same campus; points of strength and weakness due to this background are discussed. The introduction of a double cycle (undergraduate and postgraduate) according to the Bologna process (2000) and the effects on the programme structure is considered. An early phase in which professional education was emphasized at undergraduate level is recalled, which was followed by the actual revision fostering basic engineering and BME education at the first level while leaving in-depth specialization to postgraduate studies or to on-the-job training.